For none, one, or two polarities—How do POLO junctions fit best into industrial Si solar cells?. (5th November 2019) - Peibst, Robby; Kruse, Christian; Schäfer, Sören; Mertens, Verena; Bordihn, Stefan; Dullweber, Thorsten; Haase, Felix; Hollemann, Christina; Lim, Bianca; Min, Byungsul; Niepelt, Raphael; Schulte‐Huxel, Henning; et al.
Abstract: We present a systematic study on the benefit of the implementation of poly‐Si on oxide (POLO) or related junctions into p‐type industrial Si solar cells as compared with the benchmark of Passivated Emitter and Rear Cell (PERC). We assess three aspects: (a) the simulated efficiency potential of representative structures with POLO junctions for none (=PERC+), one, and for two polarities; (b) possible lean process flows for their fabrication; and (c) experimental results on major building blocks. Synergistic efficiency gain analysis reveals that the exclusive suppression of the contact recombination for one polarity by POLO only yields moderate efficiency improvements between 0.23%abs and 0.41%abs as compared with PERC+ because of the remaining recombination paths. This problem is solved in a structure that includes POLO junctions for both polarities (POLO 2 ), for whose realization we propose a lean process flow, and for which we experimentally demonstrate the most important building blocks. However, two experimental challenges—alignment tolerances and screen‐print metallization of p+ poly‐Si—are unsolved so far and reduced the efficiency of the "real" POLO 2 cell as compared with an idealized scenario. As an intermediate step, we therefore work on a POLO IBC cell with POLO junctions for one polarity. It avoids the abovementioned challenges of the POLO 2 structure, can be realized within a lean process flow, and has an efficiency benefit of 1.59%abs as compared with PERC—because not only contact recombination is suppressed but also the entire phosphorus emitter is replaced by an n+ POLO junction.